(untitled) (The International Journal for Scientific Research, 2026)
In this paper, free vibration of isotropic material Euler-Bernoulli beam resting on Pasternak foundation is considered. The governing equations of motion for isotropic beam are derived based on energy method, and Hamilton’s principle. These equations are solved using Navier’s method for simply support boundary condition. The effect of spring constant (Kw), shear constant (KG) and longitudinal wave number (m) on natural frequency (axial natural frequency and bending natural frequency) is considered. A validation is made with previous similar researches in the literature to check the accuracy of the present study. Natural frequencies are computed for various values of the parameters mentioned using MATLAB program. The beam is considered to be made of steel.